ANALISIS PERBEDAAN PENDAPATAN ASLI DAERAH (PAD) SEBELUM DAN SESUDAH PENGALIHAN PAJAK BUMI DAN BANGUNAN SEKTOR PERKOTAAN PERDESAAN (PBB-P2) - Sigit Hutomo (KINERJA, 2014)
This research is aimed to find empirical evidence on whether there is a significant difference between Regionally-Generated Income (Pendapatan Asli Daerah, or PAD) before and after the shift of the collection of Land and Building Taxes for Rural and Urban Sectors (Pajak Bumi dan Bangunan sektor Pedesaan dan Perkotaan, or PBB-P2) to regional governments. PAD is measured by local revenue sources. Three regencies/municipalities that have experienced the shift during the 2011-2013 period were selected for sampling. Secondary data were obtained from Revenue Realization Reports (Laporan Realisasi PAD) of Yogyakarta for the years 2011-2013, Revenue Realization Reports of Sleman and Bantul for the years 2012-2013, and PBB-P2 and the Sales Value of the Tax Object (Nilai Jual Objek Pajak, or NJOP) data obtained from DPPKAD. Meanwhile, primary data were obtained through interviews conducted with the PBB-P2 tax officers. The findings showed a significant differenceÂ of PAD. This, however, was not due to the shift of PBB-P2 tax collection to regional governments. The difference was caused by other revenue sources.Keywords: PBB-P2 tax collection shift, PAD